Heptacene: Synthesis and Its Hole‐Transfer Property in Stable Thin Films. Issue 41 (4th June 2021) - Miyazaki, Takaaki; Watanabe, Motonori; Matsushima, Toshinori; Chien, Ching‐Ting; Adachi, Chihaya; Sun, Shih‐Sheng; Furuta, Hiroyuki; Chow, Tahsin J.
Abstract: Heptacene (1 ) has been produced via a monoketone precursor, 2, which was prepared from 1, 2, 4, 5‐tetrabromobenzene in nine steps in a total yield of 10 %. Compound 2 was converted to 1 quantitatively by heating at 202 °C. Heptacene exhibited high thermal stability in the solid state without any observable change over two months. To investigate the potential value of 1 as a material for p‐type organic field‐effect transistors (OFETs), top‐contact OFET devices were fabricated by vacuum deposition of 1 onto a hexamethyldisilazane (HMDS)/SiO2 /Si substrate. The best hole mobility performance was 2.2 cm 2  V −1  s −1 . This is the first report of stable heptacene being used in an effective device and examined for its charge carrier properties. Abstract : Charge carrier‐bagged : Heptacene has been synthesized in nine steps in a total yield of 10 %, and its hole‐transfer properties have been measured by fabricating organic field‐effect transistor (OFET) devices. The best hole mobility performance was 2.2 cm 2  V −1  s −1 in a stable thin film of heptacene. The potential use of heptacene as an effective charge carrier is reported for the first time.